Evidence from Emerging Markets on the Effects of Integrated Reporting and Corporate Governance on the Quality of Financial and Non-Financial Reports - Dawood, Mohammed Salman (Technium Social Sciences Journal, 2025)
The research includes a focused study of the impact of implementing integrated reporting standards and corporate governance on the quality of financial and non-financial reports in economic units listed on the Iraq Stock Exchange. The research focuses on a fundamental hypothesis: optimal implementation of integrated reporting standards and the consolidation of good governance practices will substantially improve reporting quality and enhance the transparency of information available to investors and stakeholders. The research is based on a multidimensional analytical methodology combining focused theoretical and precise quantitative analysis. Advanced statistical analysis tools examine the relationship between integrated reporting, corporate governance, and reporting quality. The research also aims to provide a tangible scientific contribution that closes an existing research gap. A questionnaire was prepared to achieve the research objective, consisting of four axes and five paragraphs for each axis. The first includes measuring integrated reporting standards, the second includes measuring corporate governance, the third includes measuring the quality of financial and non-financial reports, and the fourth includes measuring the relationship between integrated reporting standards, corporate governance, and the quality of reports in general. One hundred fifty questionnaires were distributed to auditors, accountants, financial analysts, and investors. In companies, a descriptive approach was used to analyse the data. Additionally, simple linear regression was used to validate the questionnaire. The research results revealed a significant correlation and influence between implementing integrated reporting standards, the governance of economic units, and the quality of reports. Furthermore, the research showed that economic units committed to implementing integrated reporting standards and adopting good governance practices are characterised by more accurate, comprehensive, and transparent reports.